Implementasi Data Mining Untuk Menentukan Kelayakan Penerimaan Bedah Rumah Menggunakan Algoritma K-Means Fakultas Ilmu Komputer Universitas Pasir Pengaraian - Dona, Dona; Sabri, Khairul; Yasdomi, Kiki; Rifqi, Mi’rajul; Yuliansyah, Chandra; Susmita, Afnes (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
The house renovation program is a government program, namely the Public Housing and Settlement Area Office, which is shown to rehabilitate or repair community houses that are not habitabel. This program is often a problem in Bangun Purba Village because when determining house renovation assistance, it is still by looking or relying on thoughts and predictions for people who will get assistance, so that the assistance that will be distributed is not on target. This house renovation program aims to provide welfare for the poor to build or renovate houses that are not habitabel. Therefore, the author created a Data Mining system to determine the feasibility of receiving home renovation using the K-Means algorithm using the PHP programming language and MySQL database. The K-Means method utilizes training data to generate probabilities such as each grouping for different classes, so that the probability values of the grouping can be optimized to determine the eligibility for receiving home surgery assistance based on the grouping process carried out by the K-Means method.